Application of radar data for the analysis of the rainfall-runoff process in an urban catchment - Mariusz Barszcz (Acta Scientiarum Polonorum. Formatio Circumiectus)
The paper presents the results of an analysis aimed at assessing the usefulness of rainfall intensity data (maps), obtained using meteorological radar, for the estimation of the spatial distribution of rainfall amounts in the area of a small urban catchment, and their use in calculating flows using the hydrodynamic SWMM model. The analysis was carried out based on the author’s own methodology. The rainfall amounts, estimated from the radar data and measured in the studied catchment of Służewiecki Stream at two rainfall stations, for three rainfall events, significantly differed in their values depending on particular time-periods of rainfall. Based on both the estimated and the measured rainfall data, the values of their ratio were calculated, which were subsequently applied to correct the radar data obtained for the 66 virtual rain gauges in the catchment under investigation. The rainfall amounts established in these analyses were incorporated into the SWMM model, and used to calculate the flows. Based on the maximum flows that were calculated and measured in two cross-sections of the Służewiecki Stream, for the three analysed rainfall-runoff events, their conformity was assessed.